Implantation of atrial flow regulator devices in patients with congenital heart disease and children with severe pulmonary hypertension or cardiomyopathy—an international multicenter case series - Gianfranco Butera; Enrico Piccinelli; Enrico Piccinelli; Adam Kolesnik; Konstantin Averin; Cameron Seaman; Biagio Castaldi; Elena Cuppini; Alain Fraisse; Carles Bautista-Rodriguez; Sebastien Hascoet; Carmen D'Amore; et al. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe Occlutech Atrial Flow Regulator (AFR) is a self-expandable double-disc nitinol device with a central fenestration. Its use has been approved in the adult population with heart failure and described for pulmonary hypertension (PH). Only case reports and small series have been published about its use in the paediatric population and for congenital heart disease (CHD).ObjectivesThe authors sought to investigate the feasibility, safety, and short-term follow-up of AFR implantation in patients with CHD or children with PH or cardiomyopathy.MethodsThis is a multicenter retrospective study involving 10 centers worldwide. Patients of any age with CHD or patients aged < 18 years with PH or cardiomyopathy needing AFR implantation were included.ResultsA total of 40 patients underwent AFR implantation. The median age of the population at the time of the procedure was 58.5 months (IQR: 31.5–142.5) and the median weight was 17 kg (IQR: 10–46). A total of 26 (65.0%) patients had CHD, nine (22.5%) children, a cardiomyopathy, and five (12.5%), a structurally normal heart. The implantation success rate was 100%. There were two early and one late device thrombosis. Two patients (5.0%) with dilated cardiomyopathy on extracorporeal membrane oxygenator (ECMO) died during the hospital stay. At a median follow-up of 330 days (IQR: 125–593), 37 (92.5%) patients were alive. At follow-up, 20 patients improved their New York Heart Association (NYHA) class, 12 patients did not change their NYHA class, and one patient with idiopathic PH worsened.ConclusionsAFR implantation in patients with CHD and children with severe PH or cardiomyopathy is promising and seems to have beneficial effects at short-term follow-up.